Optimizing work movements to reduce injury risk: Application development with Methods-Time Measurement and WebQual analysis - Muzakir, Ari; Wahyudi, Adhie Tri; Astanti, Yuli Dwi; Kusmindari, Christofora Desi (OPSI, 2024)
Optimizing work movements is crucial for enhancing efficiency and reducing injury risks in industrial environments. Methods like Methods-Time Measurement (MTM), Work Factor (WF), and Maynard Operation Sequence Technique (MOST) are commonly used to analyze and optimize the workstations. However, there remains a lack of accessible tools for rapid and accurate time measurement. This study aims to develop a web-based and Android application designed to assist both students and professionals in calculating work times and optimizing movements (such as: material handling) more efficiently. The application was evaluated using the WebQual method, focusing on usability quality, information quality, and interaction quality. Evaluation results yielded scores of 82.3% for usability, 85.7% for information quality, and 80.5% for interaction quality. Validity and reliability tests demonstrated a Cronbach's Alpha coefficient of 87%, indicating very high reliability. The integration of MTM within this application has proven effective in accelerating work time calculations compared to manual methods and in improving movement efficiency, which directly contributes to reducing injury risks.